PROTECTIONISM OR SUSTAINABILITY? QUESTIONING EUROPEAN INTENTION ON PALM OIL BAN USING TIME SERIES DATA - Jean Richard Jokhu (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2022)
Palm oil is Indonesia’s competitive advantage in the international commodity market. Various derivative products are produced by palm oil. However, the European policy banning palm oil exports has become an obstacle to Indonesia’s palm oil export performance. Environmental issues are the reason for the ban on imports of Indonesian palm oil. However, in this research, we try to extend the view of sustainable issues. This study uses Indonesian palm oil exports and the European rapeseed oil trade to explain this issue. In this study, we try to explain a pure European policy of sustainability or protectionism. Based on the analysis results, it was found that this policy was strongly influenced by exports and production of European rapeseed oil. The effect of rapeseed oil production on palm oil imports proves that this policy has an element of protectionism to protect European rapeseed plants